2004
DOI: 10.1074/jbc.m405856200
|View full text |Cite
|
Sign up to set email alerts
|

Serglycin Is Essential for Maturation of Mast Cell Secretory Granule

Abstract: To address the biological function of the scarcely studied intracellular proteoglycans, we targeted the gene for serglycin (SG), the only known committed intracellular proteoglycan. SG ؊/؊ mice developed normally and were fertile, but their mast cells (MCs) were severely affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
223
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(246 citation statements)
references
References 50 publications
20
223
0
3
Order By: Relevance
“…Serglycin Null allele: viable; secretory granule defects in mast cells (Abrink et al 2004); dense core formation is defective in mast cell granules (Henningsson et al 2006); defective secretory granule maturation and granzyme B storage in cytotoxic T cells (Grujic et al 2005); no effect on macrophages (Zernichow et al 2006); platelets and megakaryocytes contain unusual scroll-like membranous inclusions (Woulfe et al 2008); enlargement of multiple lymphoid organs, decrease in the proportion of CD4 þ cells, more pronounced airway inflammatory response in older mice (Wernersson et al 2009); increased virulence of Klebsiella pneumoniae (Niemann et al 2007); defective regulation of antiviral CD8 þ T-cell responses (Grujic et al 2008). Agrn Agrin Null allele: embryonic lethal; reduced number, size, and density of postsynaptic acetylcholine receptor aggregates in muscles; abnormal intramuscular nerve branching and presynaptic differentiation (Gautam et al 1996(Gautam et al ,1999; smaller brains (Serpinskaya et al 1999); abnormal development of interneuronal synapses (Gingras et al 2007); increased resistance to excitotoxic injury (Hilgenberg et al 2002); reduced number of cortical presynaptic and postsynaptic specializations (Ksiazek et al 2007).…”
Section: Prg1mentioning
confidence: 99%
“…Serglycin Null allele: viable; secretory granule defects in mast cells (Abrink et al 2004); dense core formation is defective in mast cell granules (Henningsson et al 2006); defective secretory granule maturation and granzyme B storage in cytotoxic T cells (Grujic et al 2005); no effect on macrophages (Zernichow et al 2006); platelets and megakaryocytes contain unusual scroll-like membranous inclusions (Woulfe et al 2008); enlargement of multiple lymphoid organs, decrease in the proportion of CD4 þ cells, more pronounced airway inflammatory response in older mice (Wernersson et al 2009); increased virulence of Klebsiella pneumoniae (Niemann et al 2007); defective regulation of antiviral CD8 þ T-cell responses (Grujic et al 2008). Agrn Agrin Null allele: embryonic lethal; reduced number, size, and density of postsynaptic acetylcholine receptor aggregates in muscles; abnormal intramuscular nerve branching and presynaptic differentiation (Gautam et al 1996(Gautam et al ,1999; smaller brains (Serpinskaya et al 1999); abnormal development of interneuronal synapses (Gingras et al 2007); increased resistance to excitotoxic injury (Hilgenberg et al 2002); reduced number of cortical presynaptic and postsynaptic specializations (Ksiazek et al 2007).…”
Section: Prg1mentioning
confidence: 99%
“…41: 437-449 DOI 10.1002 Innate immunity 437 biological function of SG is not fully elucidated, but the results obtained from studies with SG-knockout mice suggest a role for SG in the delivery of proteins into secretory granules and/or directing the secretion of these molecules [2]. It appears that SG interacts with a plethora of molecules, playing a role in the delivery of these components into secretory vesicles and further into their targets via its highly negatively charged GAG chains.Other studies have demonstrated that SG plays a key role in the storage of mast cell proteases and granzyme B and the maturation of secretory granules of mast cells and cytotoxic T-cells [7,8]. Furthermore, SG plays a crucial role in cytotoxic T-cells, as part of a multimolecular complex with perforin and granzyme B, in the delivery of the latter to the target cells during cytotoxic cell-granule-mediated cell death [9].…”
mentioning
confidence: 99%
“…Other studies have demonstrated that SG plays a key role in the storage of mast cell proteases and granzyme B and the maturation of secretory granules of mast cells and cytotoxic T-cells [7,8]. Furthermore, SG plays a crucial role in cytotoxic T-cells, as part of a multimolecular complex with perforin and granzyme B, in the delivery of the latter to the target cells during cytotoxic cell-granule-mediated cell death [9].…”
mentioning
confidence: 99%
“…3,[11][12][13]15 We have shown that serglycin is present in promyelocytes and disappears as cells mature along the granulocytic lineage during normal myelopoiesis. 9 This prompted us to explore the expression of serglycin proteoglycan in bone marrow of AML patients and to compare with ALL patients and normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 More recently, serglycin proved to be essential both for maturation of mast cell granules and for localization of granule proteins. 13 Furthermore, granzyme B was shown to be delivered from cytotoxic lymphocytes to target cells as a macromolecular complex with serglycin. 14 The amount of granzyme B but not granzyme A nor perforin in granules is reduced in T cells lacking serglycin and the ultrastructure of granules is slightly altered.…”
Section: Introductionmentioning
confidence: 99%